Parque ciudadela nuevo Girón Santander (2020)
A study was carried out in the Ciudadela Nuevo Girón neighborhood to identify the problems of the sector, by means of surveys of the inhabitants. When analyzing the collected data, deficiencies were found in roads, lighting, security, recreation rooms, green areas, among others. The next step was to analyze the data and propose a solution to these deficiencies. At the end of the study, it was concluded that a park should be built in the Ciudadela Nuevo Girón neighborhood to meet the needs of the sector in terms of public space, recreation and recreation and to contribute to the infrastructure and development of the metropolitan area of Bucaramanga